2020
DOI: 10.1136/gutjnl-2020-321316
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal regulation of pancreatic ductal adenocarcinoma growth and molecular subtype by HNF4α and SIX1/4

Abstract: ObjectivePancreatic ductal adenocarcinoma (PDAC) is an aggressive malignancy with a 5-year survival of less than 5%. Transcriptomic analysis has identified two clinically relevant molecular subtypes of PDAC: classical and basal-like. The classical subtype is characterised by a more favourable prognosis and better response to chemotherapy than the basal-like subtype. The classical subtype also expresses higher levels of lineage specifiers that regulate endodermal differentiation, including the nuclear receptor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 85 publications
1
26
0
Order By: Relevance
“…More generally, these programs may reflect a shift towards either basal-like or terminallydifferentiated pancreatic cell states that are advantageous for surviving CRT compared to a less differentiated classical-like phenotype (Figure 3D). This model is consistent with in vitro and in vivo evidence for lineage plasticity in normal pancreatic ductal progenitor cells (102) and differentiated pancreatic cells-including a role for MYT1/MYT1L, a member of the classical neuroendocrine-like program, in ductal-neuroendocrine reprogramming (Figure 3B; Tables S3-4) (103)(104)(105)(106)(107)(108).…”
Section: Cell Programs May Contribute To Resistance Following Treatmentsupporting
confidence: 84%
See 1 more Smart Citation
“…More generally, these programs may reflect a shift towards either basal-like or terminallydifferentiated pancreatic cell states that are advantageous for surviving CRT compared to a less differentiated classical-like phenotype (Figure 3D). This model is consistent with in vitro and in vivo evidence for lineage plasticity in normal pancreatic ductal progenitor cells (102) and differentiated pancreatic cells-including a role for MYT1/MYT1L, a member of the classical neuroendocrine-like program, in ductal-neuroendocrine reprogramming (Figure 3B; Tables S3-4) (103)(104)(105)(106)(107)(108).…”
Section: Cell Programs May Contribute To Resistance Following Treatmentsupporting
confidence: 84%
“…Identifying cancer cell-and fibroblast-intrinsic programs that may govern local immune microniches remains an open question in PDAC research, with prior studies disagreeing on whether the basal-like or classicallike subtype is correlated with immune exclusion (11,89,90). Moreover, elucidating the relationships between our newly-identified neoplastic, lineage-specific programs (81,(102)(103)(104)(105)(106)(107)(108) and local immune infiltration will be critical in guiding therapeutic development.…”
Section: Modulate Local Immune Micronichesmentioning
confidence: 99%
“…1 27-30 HNF4A, in particular, was recently shown to support the classical phenotype by repressing the basal-related genes SIX1 and SIX4, among others. 31 However, Hnf4a deletion in mouse PDAC organoids was not enough to induce the full basal phenotype, suggesting that GATA6 and HNF4A have overlapping but not identical roles in maintaining lineage identity 31 and that GATA6 has a stronger antibasal function. Consistently, GATA6 loss in patient-derived samples was always broader and more pronounced than HNF4A loss, supporting a chronological hierarchy during PDAC progression towards basality (figure 2E).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from repressing FOXA1 , BACH1 activates SNAI2, which further promotes EMT, assessed by gene inactivation in human cell lines ( Sato et al, 2020 ). Transcriptomic analysis on primary tumors and patient-derived cell lines revealed that during tumorigenesis HNF4α directly activates HNF1A , and loss of the former enables a transition towards a more squamous phenotype ( Brunton et al, 2020 ; Camolotto et al, 2021 ). Moreover, HNF4α directly represses the mesodermal and neural differentiation TFs SIX1/4 , whose elevated expression was linked to the squamous subtype ( Camolotto et al, 2021 ).…”
Section: Deregulated Expression Of Transcription Factors In Tumorigenesismentioning
confidence: 99%
“…Transcriptomic analysis on primary tumors and patient-derived cell lines revealed that during tumorigenesis HNF4α directly activates HNF1A , and loss of the former enables a transition towards a more squamous phenotype ( Brunton et al, 2020 ; Camolotto et al, 2021 ). Moreover, HNF4α directly represses the mesodermal and neural differentiation TFs SIX1/4 , whose elevated expression was linked to the squamous subtype ( Camolotto et al, 2021 ). Downregulation of HNF1A is observed in the tumor vs. normal pancreas, suggesting that decreased HNF1α levels are important for PDAC tumor progression ( Hoskins et al, 2014 ; Luo et al, 2015 ).…”
Section: Deregulated Expression Of Transcription Factors In Tumorigenesismentioning
confidence: 99%